Assessment of sorghum genotypes for silage: nutritional value - Moura, Marielly Maria Almeida; Pires, Daniel Ananias de Assis; Mizobutsi, Edson Hiydu; Campos, Marcos Lopes de; Costa, Renê Ferreira; Pires Neto, Otaviano de Souza; Cristina, Leandra Soares; Sousa, Irisleia Pereira Soares de (Acta Scientiarum. Animal Sciences, 2024)
The objective of this study was to determine the agronomic characteristics, chemical composition and in situ degradability of different sorghum genotypes. The experiment was conducted at the National Maize and Sorghum Research Center – Sete Lagoas, MG. For agronomic and nutritional characteristics, a randomized block design was used, and for in situ degradability, a split-plot design was applied. Genotypes 13F2006, BRS655 and Volumax showed lower dry matter productivity compared to 12F02006 and 12F03033. Genotype BRS655 had the lowest levels of neutral detergent-insoluble fiber (NDF), acid detergent-insoluble fiber (ADF) and lignin. Furthermore, no difference was found for potential degradability (PD), indigestible fraction (IF), and effective degradability (ED) at 2; 5 and 8% hour-1 DM among the studied materials. Genotypes 12F03033 and 12F02006 combine higher productivity and nutritional quality.